(untitled) (TAJ: Journal of Teachers Association, 2018)
A large amount of protein is lost in urine along with thyroid hormones and hormone binding proteins in nephrotic syndrome (NS). This hormone loss may lead to low T4, T3 and sometimes high TSH level and often to be associated with subclinical or overt hypothyroidism. This study was done to assess thyroid dysfunction in patients with NS and to correlate thyroid hormones with albumin level of those subjects. Forty diagnosed patients of idiopathic NS and same number of age matched healthy control were selected in this study. Thyroid status was evaluated in all the subjects. In patients with NS mean (± SD) of T4, T3 and TSH were 39.34 (±29.49), 1.05 (±0.83) and 11.34 (±18.15) respectively. Mean (±SD) of T4, T3 and TSH in healthy control were 83.34 (±27.23), 2.04 (±0.70) and 2.73 (±1.79) respectively. Mean serum total T4 and T3 of patients with NS were found to be significantly lower (t= -6.935, df= 78, p<0.001 and t = -5.750, df = 78, p<0.001 respectively) and mean TSH was found to be significantly higher (t= 2.984, df = 78, p<0.01) in patients with NS as compared to healthy control. Sub clinical hypothyroidism was observed in 20 (50%) and overt hypothyroidism in 4 (10%) of patients. Significant positive correlation was found between serum albumin and serum total T4 (r = 0.818, p <0.001) and also with total T3 level (r = 0.903, p <0.001). But no correlation was found between serum albumin and serum TSH (r = - 0. 292, p>0.05) in patients with NS. So, nephrotic range proteinuria may be associated with loss of thyroid hormone in urine and can lead to subclinical or even overt hypothyroidism. TAJ 2015; 28(1): 40-44